유방암 항암화학요법 중 발생한 파상풍 - 김기현(Ki Hyun Kim); 김호영(Ho Young Kim); 정주원(Ju Won Jung); 정유승(Yu Sung Jung); 전해명(Hae Myung Jun); 박우찬(Woo Chan Park) (Annals of surgical treatment and research, 2009)
Tetanus is a neurologic disorder caused by a tetanoplasmin which is a neurotoxin elaborated by Clostridium tetani. It is characterized by increased muscle tone and spasm. Since a nationwide childhood vaccination program, tetanus has become a rare disease in Korea. Because many physicians have little experience, misdiagnosis or therapeutic delay may result in unexpected consequences. Although it has high mortality rate on attack, early detection, proper immunization and supportive care can increase survival rate. We report a case of tetanus due to puncture injury by splinter in a 69-year-old woman who has been treated with adjuvant chemotherapy of breast cancer. She was admitted to emergency room with difficulty of opening mouth for 3 days. After two days, we detected that the patient suddenly fell on her back with muscle spasm, so we diagnosed her with tetanus. She was given human tetanus immunoglobulin intramuscularly and supportive care. Forty days after admission, she was discharged without complications. Tetanus is a neurologic disorder caused by a tetanoplasmin which is a neurotoxin elaborated by Clostridium tetani. It is characterized by increased muscle tone and spasm. Since a nationwide childhood vaccination program, tetanus has become a rare disease in Korea. Because many physicians have little experience, misdiagnosis or therapeutic delay may result in unexpected consequences. Although it has high mortality rate on attack, early detection, proper immunization and supportive care can increase survival rate. We report a case of tetanus due to puncture injury by splinter in a 69-year-old woman who has been treated with adjuvant chemotherapy of breast cancer. She was admitted to emergency room with difficulty of opening mouth for 3 days. After two days, we detected that the patient suddenly fell on her back with muscle spasm, so we diagnosed her with tetanus. She was given human tetanus immunoglobulin intramuscularly and supportive care. Forty days after admission, she was discharged without complications. KCI Citation Count: 0